Injury patterns, physiological profile, and performance in university rugby union - Ball, S.; Halaki, M.; Sharp, T.; Orr, R. (International Journal of Sports Physiology and Performance, 2018)
Context: Rugby union is a physically demanding collision sport with high injury rates. There is a common perception that higher training loads result in greater injury risk in field-based sports. Objectives: To determine injury, anthropometric, and physical-performance characteristics in junior rugby union players and investigate the interaction between training load and injury across a competitive season. Design: Prospective cohort study. Methods: Fifty-one players (age 19.2±0.7 y) from an under-20 university rugby union team (forwards, n=27; backs, n=24) participated in a study conducted over a competition season. Training load, injury characteristics, anthropometry, physiological performance, and match time-loss injury incidence were observed. Results: Backs had significantly lower body mass (ES [95% CI]=1.6 [0.9, 2.2]), skinfold thickness (ES=1.1 [0.5, 1.7]), strength (squat ES=0.6 [0.0, 1.2], deadlift ES=0.6 [0.0, 1.1], bench press ES=0.9 [0.4, 1.5]), lower-body power (ES=0.4 [-0.2, 1.0]), and higher maximal aerobic capacity (ES=-0.3 [-0.8, 0.3]) than forwards. Match injury incidence was 107.3 injuries/1000 player hours (forwards 91.4/1000, backs 125.5/1000) during preseason and 110.7 injuries/1000 player hours (forwards 124.1/1000, backs 95.2/1000) during in-season. Forwards showed higher incidence of joint and ligament (P=.049) and upper-limb (P=.011) injuries than backs. No significant relationship between overall training load and match injury incidence was found. However, lower match injury incidence was associated with higher weekly training volume in backs (P=.007). Conclusions: Positional differences in body composition, performance, injury characteristics, and match injury patterns were identified in junior university rugby union players, indicating the need for position-specific training programs to reduce risk of injury.